# How do you find the vertex of y = -3x² + 6x -4.

**Solution:**

Given equation y = -3x² + 6x - 4.

this is of the form a = -3, b = 6 and c = -4

The general vertex form of the parabola of a(x-h)² +k

where the vertex is represented as (h, k)

To get vertex form we need to expand -4 as -3 and -1

y= −3x² + 6x -3-1

y= −3(x² - 2x +1) -1

y= −3(x -1)² -1

This is in standard vertex form y= -a(x-h)² +k

So, we get vertex as (1, -1)

## How do you find the vertex of y = -3x² + 6x -4.

**Summary: **

We find the vertex of y = -3x² + 6x - 4 by splitting the constant.

Math worksheets and

visual curriculum

visual curriculum